Light regulation of light‐harvesting antenna size substantially enhances photosynthetic efficiency and biomass yield in green algae†. (20th April 2020) - Negi, Sangeeta; Perrine, Zoee; Friedland, Natalia; Kumar, Anil; Tokutsu, Ryutaro; Minagawa, Jun; Berg, Howard; Barry, Amanda N.; Govindjee, Govindjee; Sayre, Richard
Summary: One of the major factors limiting biomass productivity in algae is the low thermodynamic efficiency of photosynthesis. The greatest thermodynamic inefficiencies in photosynthesis occur during the conversion of light into chemical energy. At full sunlight the light‐harvesting antenna captures photons at a rate nearly 10 times faster than the rate‐limiting step in photosynthetic electron transport. Excess captured energy is dissipated by non‐productive pathways including the production of reactive oxygen species. Substantial improvements in photosynthetic efficiency have been achieved by reducing the optical cross‐section of the light‐harvesting antenna by selectively reducing chlorophyll b levels and peripheral light‐harvesting complex subunits. Smaller light‐harvesting antenna, however, may not exhibit optimal photosynthetic performance in low or fluctuating light environments. We describe a translational control system to dynamically adjust light‐harvesting antenna sizes for enhanced photosynthetic performance. By expressing a chlorophyllide a oxygenase ( CAO ) gene having a 5′ mRNA extension encoding a Nab1 translational repressor binding site in a CAO knockout line it was possible to continuously alter chlorophyll b levels and correspondingly light‐harvesting antenna sizes by light‐activated Nab1 repression of CAO expression as a function of growth light intensity. Significantly,  algae having light‐regulated antenna sizes had substantially higher photosynthetic rates and two‐fold greater biomass productivity than the parental wild‐type strains as well as near wild‐type ability to carry out state transitions and non‐photochemical quenching. These results have broad implications for enhanced algae and plant biomass productivity. Significance Statement: The greatest thermodynamic inefficiencies in photosynthesis occur during the conversion of light into chemical energy. This is due to the mismatch between photon capture rates at full sunlight intensities and downstream constraints in electron transport. By engineering a dynamically self‐adjusting light‐harvesting antenna size system, we have substantially improved photosynthetic efficiency in green algae and increased biomass productivity by two‐ to three‐fold.